(untitled) (Bangladesh Journal of Otorhinolaryngology, 2014)
Objective: To assess the rate of graft take and hearing improvement after myringoplasty. Methods: This cross sectional study was carried out among sixty (60) patients those who were admitted into the Department of Otolaryngology & Head-Neck Surgery, Dhaka Medical College Hospital and BSMMU with their descriptive history, clinical findings, pre and postoperative hearing assessment by PTA during the period of June 2006 to December2006. Results: Sixty cases were diagnosed as CSOM (tubo-tympanic) disease and underwent myringoplasty. The lowest and highest age of the patients at presentation was 15 and 45 years respectively with a mean age of 27 years. The overall success rate was 80% (48 out of 60). The surgical failure was 20% (12 out of 60) and those were graft failure, re-perforation & anterior blunting at the last visit. Graft failure occurred during the first 8 weeks in 3 cases out of the 12 cases. Conclusion: Myringoplasty is a valid treatment modality for tubo-tympanic type of CSOM. DOI: http://dx.doi.org/10.3329/bjo.v19i2.17635 Bangladesh J Otorhinolaryngol 2013; 19(2): 119-123